THE EFFECT OF GRAPHIC ORGANIZER WITH SCHOOLOGY ON STUDENTS’ WRITING SKILL AT MA MASYHUDIYAH GIRI - Cahyaningtias, Betty Indah; Anwar, Khoirul; Ma’rifah, Ulfatul (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2020)
Writing is a productive skill which makes the students managing the ideas into texts or paragraphs. Writing skill is one of the things that noticed by the Indonesian Minister of Education and Culture. It can be seen at the curriculum. The curriculum expects that the students will be able to write in English texts well at the end of learning process. However to reach the goal at curriculum is not easy. It because the students have a lot of problems in learning writing. For instance, when the students write paragraph, they usually has no unity so the content of each paragraph did not appropriate with the topic. Then, the students difficult to organize ideas properly. Besides that, the students also difficult to choose the appropriate words. These problems are caused by the ways students learn writing are not really effective. To solve the problems, the researcher use Graphic Organizer with Schoology as the alternative in teaching writing. This study was investigate the significant effect of Graphic Organizer with Schoology on Students’ Writing Skill. The researcher chose eleventh grade at MA Masyhudiyah Giri to conduct this study. The sample was 11 MIPA 2 as the experimental group and 11 MIPA 3 as the control group. Both of class consisted of 30 students. So, the number of the participants in this study was 60 students. The research finding showed that there was a signinificant difference between experimental group who were taught by using graphic organizer with schoology and control group who were taught by only using graphic organizer. It is proven by the result of sig. (2-tailed) is lower than 0.05 (0.000<0.05). So, the null hypothesis can be rejected. It means that Graphic Organizer with Schoology has significantly effects on students’ writing skill. Therefore, the researcher suggest to the English teacher for Implementing of Graphic Organizer with Schoology as the alternative in teaching writing. For the future researcher, the researcher hopes that can use Graphic Organizer with Schoology in different way to develop other skill such as reading skill to make a difference with this study